Factors Affecting the Welfare of Unweaned Dairy Calves Destined for Early Slaughter and Abattoir Animal-Based Indicators Reflecting Their Welfare On-Farm - Boyle, Laura A.; Mee, John F. (Frontiers in Veterinary Science, 2021)
In many dairy industries, but particularly in pasture-based industries operating seasonal calving, ‘surplus calves’, which are mostly male, are killed at a young age because they are of low value and it is not economically viable to raise them. Such calves are either killed on farm soon after birth or sent for slaughter at an abattoir. In countries where calves are sent for slaughter the age ranges from 3-4 days (New Zealand and Australia; ‘bobby calves’) to 3-4 weeks (e.g. Ireland); they are not weaned. All calves are at the greatest risk of death in the first month of life but when combined with their low value, this makes surplus calves destined for early slaughter (i.e. <1 month of age) particularly vulnerable to poor welfare while on-farm. The welfare of these calves may also be compromised during transport and transit through markets and at the abattoir. There is growing recognition that feedback to farmers of results from animal-based indicators (ABI) of welfare (including health) collected prior to and after slaughter can protect animal welfare. Hence, the risk factors for poor on-farm, in-transit and at-abattoir calf welfare combined with an ante and post mortem (AM/PM) welfare assessment scheme specific to calves <1 month of age are outlined. The following ABIs, at individual or batch level, are proposed: AM indicators include assessment of age (umbilical maturity), nutritional status (body condition, dehydration), behavioural status (general demeanour, posture, able to and stability while standing and moving, shivering, vocalisations, oral behaviours/cross-sucking, fearfulness, playing), and evidence of disease processes (locomotory ability [lameness], cleanliness/faecal soiling [scour], injuries hairless patches, swellings, wounds], dyspnoea/coughing, nasal/ocular discharge, navel swelling/discharge); PM measures include assessment of feeding adequacy (abomasal contents, milk in rumen, visceral fat reserves) and evidence of disease processes (omphalitis, GIT disorders, peritonitis, abscesses [internal and external], arthritis, septicaemia, and pneumonia). Based on similar models in other species, this information can be used in a positive feedback loop not only to protect and improve calf welfare but also to inform on-farm calf welfare management plans, support industry claims regarding animal welfare and benchmark welfare performance nationally and internationally.